2013
DOI: 10.1007/s11010-013-1586-x
|View full text |Cite
|
Sign up to set email alerts
|

Silence of ezrin modifies migration and actin cytoskeleton rearrangements and enhances chemosensitivity of lung cancer cells in vitro

Abstract: Ezrin, primarily acts as a linker between the plasma membrane and the cytoskeleton, is involved in many cellular functions, including regulation of actin cytoskeleton, control of cell shape, adhesion, motility, and modulation of signaling pathways. Although ezrin is now recognized as a key component in tumor metastasis, its roles and the underlying mechanisms remain unclear. In the present study, we chose highly metastatic human lung carcinoma 95D cells, which highly express the ezrin proteins, as a model to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Previous studies of tumor metastasis suggested that strongly and weakly invasive cancer cells differ in terms of the reorganization of the actin cytoskeleton[37]. Chen et al found that knockdown of the expression of the actin cytoskeleton protein ezrin contributed to sensitizing lung cancer cells to cisplatin and pirarubicin[38]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of tumor metastasis suggested that strongly and weakly invasive cancer cells differ in terms of the reorganization of the actin cytoskeleton[37]. Chen et al found that knockdown of the expression of the actin cytoskeleton protein ezrin contributed to sensitizing lung cancer cells to cisplatin and pirarubicin[38]. …”
Section: Discussionmentioning
confidence: 99%
“…Expression levels of ezrin were found to be significantly higher in primary cancer tissues than matched normal lung tissues [23]. Suppression of ezrin expression in NSCLC cell lines leads to reduced migration and invasion, anchorage-independent growth ability, and increased drug sensitivity [24].…”
Section: Introductionmentioning
confidence: 94%
“…Its direct target is ezrin, an important member of the ezrin-radixin-moesin (ERM) family. Ezrin functions as a cross-linker between the actin cytoskeleton and the plasma membrane, and is intimately associated with cancers including chondrosarcoma, Ewing's sarcoma and lung cancer [42][43][44]. Studies from our own and other groups have demonstrated that overexpression of ezrin promotes invasion, migration and metastasis of OS cells [45], but ezrin silencing or its small molecule inhibitors NSC305787 and NSC668394 protect against OS development [46,47].…”
Section: Mir-183mentioning
confidence: 99%